Critical thinking of extrovert boys in problem solving - M I E Budiarti; Ruslan Ruslan; M S Kahar (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The purpose of this research is to know the ability of critical thinking of Extrovert Boys in Problem Solving. This research used qualitative descriptive that conducted at di SMP Muhammadiyah 8 and the students of VII grade as subject and the object is critical thinking skill in problem solving. It used Eysenck Personality inventory-A (EPI-A) test for the instrument which conducted in the first meeting to all students, problem solving test was given to 6 extrovert boys and interview. Problem solving strategy used to know critical thinking skill by giving personality EPI-A test in the first meeting on students of VII grades to find respondents, 6 extrovert boys. After finding the respondents,the next step is giving problem solving test. The researcher interviewed the result of respondents. Findings showed that : 1) High critical thinking of extrovet boys werenot success in strategy step, only in alternative solution; 2) Moderate critical thinking of extrovet boys werenot success in strategy step, only in alternative solution, and 3) Low critical thinking of extrovet boys werenot success in inference and strategy step.